Heavy Mn2+-doped near-infrared photon upconversion luminescence in fluoride RbZnF3:Yb3+, Mn2+ guided by dopant distribution simulation. Issue 35 (12th August 2020) - Han, Xinxin; Song, Enhai; Zhang, Shuai; Ye, Shi; Yang, Xiao-Bao; Zhang, Qinyuan
Abstract : NIR UC emission was observed in heavy Mn 2+ -doped RbZnF3 :Yb 3+, Mn 2+ designed by the dopant-distribution prediction simulation. The GSA/ESA and GSA/ETU models of the super-exchange-coupled Yb 3+ –Mn 2+ –Mn 2+ trimer are proposed for the NIR UC emission. Abstract : Mn 2+ ions-activated phosphors play a crucial role in modern lighting and display due to their typical tunable single-band visible (VIS) emission characteristics. Herein, besides the conventional VIS emission, a near-infrared (NIR) emission centered at ∼780 nm is presented in heavy Mn 2+ -doped fluoride RbZnF3 :Yb 3+, Mn 2+ designed by the dopant-distribution prediction simulation. On varying the dopant (Mn 2+ ) concentration, the single-band VIS emission to VIS/NIR dual emission and then to pure NIR photon upconversion (UC) emission was achieved in RbZnF3 :Yb 3+, Mn 2+ . The density functional theory (DFT) calculations, static and dynamic luminescence analysis, as well as the extended-X-ray absorption fine structure (EXAFS) characterization strongly confirmed that the NIR emission of the Mn 2+ was from the Mn 2+ –Mn 2+ dimer induced by Mn 2+ ions aggregation in RbZnF3 . Further, a ground-state absorption (GSA)/excited state absorption (ESA) NIR UC luminescence mechanism based on the Yb 3+ –Mn 2+ –Mn 2+ trimer model is proposed. This work provides a new strategy for realizing single-band NIR photon UC emission, and also provides new insights into the rational design of the Mn 2+ VIS/NIR emission via dopant-distribution prediction.